Larry Crowne [videorecording (DVD)] - Hanks, Tom; Roberts, Julia, 1967-; Ortega, Roxana (Universal, 2011)
When he suddenly finds himself without his long-standing blue-collar job, Larry Crowne enrolls at his local college to start over. There, he becomes part of an eclectic community of students and develops a crush on his teacher. Now this simple guy will discover that when you think everything worth having has passed you by, you just might find your reason to live.